GEOLOGICAL AND INDUSTRIAL FEATURES OF DISCLOSURE AND TESTING OF LOW-PERMEABLE GAS-SATURATED SEDIMENTS - Khomyn, V.; Tsyomko, V.; Goptarova, N.; Bronitska, N.; Trubenko, А. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The relevance of research is attributed to the scientific justification of the features of disclosure and testing of low-permeable gas perspective deposits. Under the low-permeable gas perspective deposits in the Carpathian region of Western Ukraine, we consider the rocks of the Cretaceous system (based on previous works). Deposits of the Cretaceous system in the cross section of the Carpathian region occupy more than half the volume of the rock mass within the boundaries of the flysch strata, and the bulk in the depth interval 1.5–3.5 km corresponds to the sediments of the Stryiska suite of the upper section of the Cretaceous system. That is, the object of research is quite significant in its volume. In selecting the perforation intervals and methods of secondary action on the productive layer in wells drilled in regions where low-permeable thin-layered flysch formations (thin interlayering sandstones, siltstones and mudstones) are observed, we propose a method by which the choice of methods of secondary action on the layer, the intervals of mudstone is justified. In this case, the gas perspective deposits (due to the increase in the permeability of the mudstone layers during their perforation, and later also during the hydraulic fracturing of the layer) are combined into one significant in thickness gas-bearing exploitation object, which increases the flow of gas into the wells. Target disclosure of the gas horizons and increase of their gas output to optimal geological and economic parameters require the use of new technologies, similar to those used in the extraction of gas from shale rock. The simulation of the hydraulic fracturing process of the sand-mudstone pack of Upper Cretaceous deposits in the range 3260–3330 m in the well 2-Tarasivka with the Meer MFrac program proved an increase of the fixed crack opening (in this case, from 0.02 to 0.22 cm), which will contribute to significant increase in the conductivity of the crack from 668 to 6000 mD·m, and it is an important factor in the extraction of hydrocarbon gas from low-permeable deposits, which will increase the productivity of wells. And this will contribute to a significant increase in the fuel and energy supply of Ukraine by its own hydrocarbon raw material.
Keywords: gas-bearing; hydraulic fracturing of the layer; Upper Cretaceous deposits; gas perspective objects